Artes de contar, exercício de rememorar: história, memória e narrativa dos índios pitaguary - Pinheiro, Joceny de Deus (2002)
Art of Telling, Exercise of Recollecting: History, Memory and Narratives of Indian Pitaguary is a work of anthropological research on the role of memory in a context where indigenous identification processes begin to multiply. The study thus focuses on the stories of leaders and storytellers residents in the area that today is known as TI - Indigenous Land Pitaguary. In the first chapter, I explain what is here termed the "coming and going of research," a kind of background and reporting of field work, leaving a glimpse of the way we started the research and development period in which each of its steps. It is also this first chapter I present the narrators and situations of narration, describing some of the events I considered important during the search. In the second chapter, I explain, albeit briefly, the framework in which we built the object "Indians of the Northeast" and the various visions that persist about the existence of them - representations in general negative. Moreover, there is also that I introduce a discussion of the criteria for identifying ethnic groups and their nature. Then the chapter is divided into two: part of the Northeast, the state of Ceara, and finally, part of the town of St. Anthony of Pitaguary. The idea that guides this sorting is that it is necessary for the understanding of reality that takes place in the town they live in the Pitaguary, understanding what is happening in the bigger picture is that the state, which in its turn, is housed in a context that is even greater in the Northeast Region. For this, I refer to previous studies about indigenous groups present in Ceara and other states in the Northeast. Even late in the second chapter, I bring to the text some of the existing documents on the group Pitaguary, quoting from some of those who mention the names of the localities in which they live (or lived in the corresponding period), the geographical features (rivers, saws, etc..) and even previous generations who have their names cited in full in a document of Land Registry. After attempting to contextualize the historical and geographical group, the third chapter is intended to fully Pitaguary the narratives, exploring its key issues, interests and possible directions. So it appears that the narratives about the "time of slavery" on the "holy hose," "nature", the "unlucky", the "Toré. Between exposure and over narration, presenting the theoretical ideas that guide the research about what happens to be the memory of a group or its operation. In the fourth chapter, the discussion of narrative continuity wins, now focusing on the passage of time - from past to present. For this reason, the text is divided into two sections: 1) the past: the time of the denial of identity and 2) the present-time assertion. In these two stages that differ in several others, are contained, first, the stories that deal with the "captivity", the trapping of the older buildings to work on the dam and the church, conflicts with the many farmers and other lords. Secondly, there are the narratives that concern the time of affirmation of the group. In general, stories are focused on the story of what is called the "struggle" as well as for the evidencing of what they consider signs of distinction, as knowledge of the shaman, medicine "forest" indigenous and self-learning. In the fifth and final chapter, I explain important concepts for clarifying the relationship between memory, narrative and identity of the group Pitaguary, thinking, even in relation to that memory has the political mobilization of the same. The references that guide me in understanding the concept of memory more clearly appear in this chapter, which is tested as a kind of completion of work, made shortly after